2017
DOI: 10.1016/j.numecd.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Resting heart rate and the risk of cardiovascular disease, total cancer, and all-cause mortality – A systematic review and dose–response meta-analysis of prospective studies

Abstract: This meta-analysis found an increased risk of coronary heart disease, sudden cardiac death, heart failure, atrial fibrillation, stroke, cardiovascular disease, total cancer and all-cause mortality with greater resting heart rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
145
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 201 publications
(180 citation statements)
references
References 121 publications
13
145
0
8
Order By: Relevance
“…The association was stronger in low‐risk groups, and significant joint association was found between RHR and other known risk factors in respect to T2D risk. Taken together with accumulating evidence suggesting the usefulness of RHR as a diagnostic tool for several chronic diseases and a prognostic tool for patients, our findings suggest that RHR has a potential to be used independently, and in addition to other known risk factors, to predict future T2D in the clinical settings.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The association was stronger in low‐risk groups, and significant joint association was found between RHR and other known risk factors in respect to T2D risk. Taken together with accumulating evidence suggesting the usefulness of RHR as a diagnostic tool for several chronic diseases and a prognostic tool for patients, our findings suggest that RHR has a potential to be used independently, and in addition to other known risk factors, to predict future T2D in the clinical settings.…”
Section: Discussionsupporting
confidence: 62%
“…Resting heart rate (RHR) has been commonly used as a simple and useful diagnostic and predictive tool for cardiovascular disease in clinical settings . More recently, epidemiological studies have found an association between elevated RHR and increased risk of T2D, after adjusting for potential confounders .…”
Section: Introductionmentioning
confidence: 99%
“…The Kailuan study analysed 92 562 participants and reported that cardiovascular risk in highest quintile group compared with the lowest quintile group of RHR was similar, whereas the risk of all‐cause death was 18% higher . Recently, published meta‐analysis that involved 87 studies showed that increase of RHR per 10 bmp elevated risk for cardiovascular disease occurrence by 15% and for all‐cause mortality by 17% . The analysis of 112 680 subjects demonstrated that subjects with RHR >80 bpm compared with those with RHR <65 bmp had 44% greater cardiovascular risk and even 54% higher total mortality …”
Section: Heart Rate and Cardiovascular Morbidity And Mortalitymentioning
confidence: 99%
“…The Kailuan study showed that the risk of myocardial infarction was 10% higher in the highest quintile group compared with the lowest quintile RHR group . Aune et al in the large meta‐analysis recently revealed that increase of RHR per 10 bmp elevated the risk for coronary heart disease by 7% and 9% for sudden cardiac death. Large meta‐analysis that involved 1 227 511 participants reported that an increment of RHR by 10 bpm elevated the risk of coronary artery disease for 12%, whereas Wang et al demonstrated that higher RHR was related to more severe coronary artery disease.…”
Section: Heart Rate and Risk Of Coronary Artery Diseasementioning
confidence: 99%
See 1 more Smart Citation